(untitled) (Journal of Soft Computing Exploration, 2023)
The term "tunanetra" is used to refer to someone who experiences total blindness or visual impairment. Such visual limitations result in visually impaired individuals facing difficulties in accessing information quickly and performing daily activities like walking, driving, and more. Walking is one of the crucial activities for visually impaired individuals because it is one way to explore the world and engage in daily activities. Based on this issue, an assistive device for the visually impaired was designed using embedded system technology. In 2022, Serly Juliana Taneo, Jonshon Tarigan, Frederika Rambu Ngana, and Andreas Ch. Louk developed a mobility aid device for individuals with visual impairments using ultrasonic sensors for distance detection and Arduino as the microcontroller. However, the device primarily focused on mobility, and there is a need to add new features, such as emergency information using SMS technology that can send messages with the press of a button. The research results indicate that the ultrasonic sensor successfully triggers vibrations within a range of 1-100 cm, and the button can send emergency notifications via SMS when pressed. Therefore, it can be concluded that all connected components can function as intended. By combining SMS technology and ultrasonic sensors, this assistive device is expected to enhance the safety and independence of individuals with visual impairments as they navigate their surroundings.